Legal Protection Of Buyers Against Land Mafia Crimes In The Making Of Sale And Purchase Deeds - Aslan Noor; Aditya Pratama; Anjas Arlianzha; Lukman Lutfianto; Senator Giovani Putra Arlond (Magister Kenotariatan Universitas Pasundan, 2023)
This research discusses the legal protection for buyers in the context of land mafia crimes related to the making of a sale and purchase deed. Land mafia crimes have become a serious threat to property transactions, especially when involved in the creation of sale and purchase deeds. The purpose of this research is to analyze the legal protection available for buyers in dealing with land mafia crimes. This research uses the normative legal research methods by analyzing laws and regulations relating to property transactions and legal protection for buyers. The results showed that legal protection for buyers can be found in several legal instruments, such as the Basic Agrarian Law, the Law on Land Rights Guarantees, and the Law on Provincial Regulations on Spatial Planning. However, there are several challenges faced by buyers in protecting their rights related to property purchases. Land mafia crimes often involve complex practices and deception that are difficult to detect. In addition, vulnerabilities in the sale and purchase deed process and weak law enforcement are obstacles in providing effective protection for buyers. In this research, improvements are recommended in the legal system related to property transactions to provide stronger protection for buyers. Awareness-raising and education effort for the public are also important to prevent property deception and land mafia crimes. In addition, it needs to be close cooperation between the authorities, financial institutions and the public to tackle this problem. In conclusion, the legal protection for buyers in the context of land mafia crimes in making of sale and purchase deeds still requires serious attention. Improvement of law and regulations, increasing public awareness, and cooperation between institutions can help strengthen legal protection for property buyer.